Analyzing Effective Project Management Approaches to Reduce LNG Environmental Footprint - Sadat Itohan Ihwughwavwe; Gloria Siwe Usiagu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The escalating global demand for energy has propelled Liquefied Natural Gas (LNG) to the forefront of the energy landscape. However, this surge in LNG prominence is accompanied by escalating environmental concerns. This paper offers a meticulous examination of the intricate interplay between project management methodologies and environmental sustainability, with a specific focus on how strategic approaches can effectively curtail the environmental impact of LNG projects. Commencing with a contextualizing overview of the burgeoning role of LNG in the energy sector, the paper emphasizes the urgency of addressing environmental challenges associated with LNG development. A foundational analysis underscores the pivotal role of project management in aligning LNG projects with sustainability objectives. The subsequent exploration delves into the specific environmental challenges ingrained in LNG projects, elucidating the ecological implications across various stages, from liquefaction processes to transportation and facility operations. Seamlessly transitioning, the paper then dissects the efficacy of various project management approaches, casting a spotlight on sustainable supply chain management. Here, the focus extends to the practical implementation of green procurement and ethical sourcing as instrumental mechanisms for diminishing environmental impact. Continuing this trajectory, the analysis delves into the integration of technology, examining innovative liquefaction processes and the infusion of renewable energy into LNG facilities as strategic imperatives. Simultaneously, the importance of stakeholder engagement is underscored, emphasizing community involvement and strategic partnerships as key drivers for navigating complex regulatory landscapes. Further bolstering the narrative, the paper presents a series of meticulously examined case studies, offering not only illustrative examples of successful environmentally-conscious LNG projects but also distilling lessons learned from these endeavors. In essence, this paper strives to present a thorough, evidence-driven exploration of the intricate relationship between project management methodologies and environmental sustainability within the realm of LNG projects.